Indulekha - Chandumenon, O. (Ōyyārattu), 1847-1899.; Devasia, Anitha (New Delhi ; New York : Oxford University Press, 2005)
Novel based on Nair community of Kerala, who practices matrilineal family system.
FOREWORD BY SUSIE THARU ; PREFACE ; ACKNOWLEDGEMENTS ; BEGINNINGS ; INDULEKHA ; AN ANGRY MAN'S OATH ; A SEPARATION ; PANCHUMENON'S ANGER ; PANCHUMENON'S ANXIETY ; KANNAZHI MOORKILLATHA MANAKKAL SURINAMBUTHIRIPAD ; AN ARRIVAL FROM MADRAS ; THE COMING OF THE NAMBUTHIRIPAD AND OTHER THINGS ; A LETTER FROM MADRAS ; WHAT PEOPLE SAID ABOUT THE NAMBUTHIRIPAD ; CONVERSATION BETWEEN INDULEKHA AND THE NAMBUTHIRIPAD ; SECOND CONVERSATION BETWEEN INDULEKHA AND THE NAMBUTHIRIPAD ; THE NAMBUTHIRIPAD'S WEDDING ; A CALAMITY ; MADHAVAN'S TOUR OF THE COUNTRY ; HOW MADHAVAN WAS FOUND ; A CONVERSATION ; THINGS WHICH ACTUALLY HAPPENED AT HOME DURING THE PERIOD OF MADHAVAN'S JOURNEY ; THE END OF THE STORY ; AFTERWORD ; APPENDICES ; BIBLIOGRAPHY ; GLOSSARY
Novel.
Includes bibliographical references (p. [275]-283)
ENH
HYE Trade International
Keywords: Malayalam literature -- Novel -- 20th century; Nairs -- Social conditions -- Fiction; India